PERBEDAAN KONSUMSI BUAH NANAS SEGAR DENGAN BUAH NENAS OLAHAN TERHADAP PENURUNAN TINGGI FUNDUS UTERI PADA IBU NIFAS NORMAL DI PMB ROSITA KOTA PEKANBARU - Yeni Aryani; Fatiyani Alyensi; Okta Vitriani (STIKes Al-Insyirah Pekanbaru, 2023)
In postpartum women, the process of returning the uterus to its pre-pregnant form is very important for increasing uterine contractions which can accelerate the involution process. This study aims to compare the effectiveness of consumption of fresh pineapple with processed pineapple (dried pineapple) to decrease uterine fundal height in normal postpartum mothers. This type of research is a quasi-experimental research design with two-groups pre-test-post-test design. The study was conducted at PMB Rosita Pekanbaru City with a population of all postpartum women giving birth at PMB Rosita from February to July 2022 with a sample of 36 people divided into 18 respondents consuming fresh pineapple and 18 consuming dried pineapple (pineapple chips). The sampling technique is purposive sampling. The results of data analysis showed that the average decrease in uterine fundus height after the intervention was an average of 12.17 cm for fresh pineapple consumption and 5.13 cm for processed pineapple fruit consumption (mean). Data analysis using independent t test consumption of fresh pineapple is more effective in accelerating the decrease in uterine fundal height compared to processed pineapple (dried pineapple) with a value of (p: 0.000). It is hoped that this research can be useful for health workers in providing education to postpartum mothers by utilizing pineapple to accelerate the decrease in uterine fundal height.